Analysis of the Impact of Financial Structure Evolution on Economic Growth and Management Efficiency - Zuo, Zhouwei (Wireless communications and mobile computing, 2022)
Under the development of social economy and the gradual improvement and optimization of the financial and economic system, China’s financial structure is constantly changing and evolving. Financial institutions are the interrelations and connections between the various parts of the economy as a whole. They represent the role and achievements of the financial economy. Research shows that the transformation and evolution of financial structure promotes economic development and management efficiency. Therefore, under the background of the continuous evolution of financial structure, this article explores the factors of the evolution of financial structure on economic growth and management efficiency. The results of the experiment are as follows: (1) this article investigates developments of the evolution of financial structure, economic development, and management efficiency, determines the research direction of the experiment, provides background support for the subject research of this paper, and explores the influencing factors according to the impact mechanism on economic development and management efficiency and (2) put the evolution background of the financial structure in the degree of economic development and management efficiency. By using the economic growth calculation algorithm and management efficiency calculation algorithm, calculate the change trend of the range of economic growth and the fluctuation of the degree of management efficiency under the background of the evolution of the financial structure. The experimental results show that under the background of the evolution of the financial structure, the total development of the national economy has been effectively broken through, and the management mode of enterprises has been improved to effectively improve the management efficiency.